2009
DOI: 10.1016/j.juro.2008.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Visually Directed Transrectal High Intensity Focused Ultrasound for the Treatment of Prostate Cancer: A Preliminary Report on the Italian Experience

Abstract: A favorable outcome of high intensity focused ultrasound is associated with lower baseline prostate specific antigen, lower prostate specific antigen nadir, lower Gleason score and lower tumor stage. As with any novel technology long-term data will be required before this technique gains widespread clinical acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 19 publications
1
45
0
Order By: Relevance
“…However, comparing these outcomes with previous studies is not feasible due to the heterogeneity in patient selection and the definition of biochemical failure. Some authors have defined biochemical failure using the ASTRO definition (three consecutive PSA rises) [3,10,13], whereas more recent studies, including our study, have used the Phoenix criteria [1,[8][9]. Although the definitions of BFSR and DFSR in our study were similar to those in Blana's study [8], they excluded higher risk patients (cT2c, Gleason score 17, preoperative PSA 120 ng/ml), so that their results cannot be compared directly to our own.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, comparing these outcomes with previous studies is not feasible due to the heterogeneity in patient selection and the definition of biochemical failure. Some authors have defined biochemical failure using the ASTRO definition (three consecutive PSA rises) [3,10,13], whereas more recent studies, including our study, have used the Phoenix criteria [1,[8][9]. Although the definitions of BFSR and DFSR in our study were similar to those in Blana's study [8], they excluded higher risk patients (cT2c, Gleason score 17, preoperative PSA 120 ng/ml), so that their results cannot be compared directly to our own.…”
Section: Discussionmentioning
confidence: 90%
“…We found that subclinical strictures were difficult to detect and would likely not have been registered without following CTC-NCI version 3.0 criteria. Most literature reports likely considered only grade 3 or 4 strictures [1,[8][9][10]. We considered 20.8% of patients to have SCUS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, careful selection when treating patients with primary HIFU is essential, since there is a large range in BF rate (15-50%), which varies depending on risk group at diagnosis [4,13]. Little is known about the best treatment option at relapse, mainly because the current evidence is mostly based on small series, usually with a short median follow-up, making it very difficult to draw any definitive conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…These results concur with other recent reports. 15,16 We used the Phoenix definition plus histological results as a basis for judgment of disease-free survival, since we were not satisfied with other definitions currently used to measure the efficacy of HIFU treatment. Recently, specific criteria for assessment of HIFU have been proposed (the Stuttgart criteria), 17 and we intend to compare the results based on the Phoenix-ASTRO and Stuttgart criteria in a future study.…”
Section: Discussionmentioning
confidence: 99%